Successful Use of Extracorporeal Membrane Oxygenation for the Treatment of Cardiogenic Shock due to Scorpion Envenomation - Amine Tarmiz; Imene Mgarrech; Chokri Kortas; Sofiane Jerbi (Case Reports in Critical Care)
Introduction. The occurrence of a cardiogenic shock is a rare presentation after scorpion envenomation. The treatment includes classically the use of inotropes and specific vasodilators. Case Presentation. We report a case of an 11-year-old boy presenting with cardiogenic shock and pulmonary edema after a scorpion sting. Despite adequate management at the emergency department and intensive care unit, the patient’s hemodynamic status worsened rapidly, justifying his transfer to our department for ventricular mechanical assistance by venoarterial extracorporeal membrane oxygenation. The following outcomes were favorable and the boy was discharged home on day 29 without aftereffects. Conclusion. This is the first report of successful use of extracorporeal membrane oxygenation for the treatment of cardiogenic shock after scorpion envenomation.